The role of trunk muscle strength for physical fitness and athletic performance in trained individuals: A systematic review and meta-analysis - Prieske, O.; Muehlbauer, T.; Granacher, U. (Sports Medicine, 2016)
Background: The importance of trunk muscle strength (TMS) for physical fitness and athletic performance has been demonstrated by studies reporting significant correlations between those capacities. However, evidence-based knowledge regarding the magnitude of correlations between TMS and proxies of physical fitness and athletic performance as well as potential effects of core strength training (CST) on TMS, physical fitness and athletic performance variables is currently lacking for trained individuals.